Urological Cancer Management - Al-Mamari, Said Abdallah; Al-Busaidy, Salim Said (Springer International Publishing : Imprint: Springer, 2015)
This succinct text provides the reader with essential guidelines on the management of common urological malignancies, giving the reader precise details on risk factors, clinical and investigative assessment, staging and treatment. Urological Cancer Management assists the reader in assimilating salient points through easy learning and unique illustrations. This informative text is the perfect go-to for medical students, paramedical trainees as well as urological residents and consultants who wish to learn more about new concepts and advances reported in recent literature.